Case Report: Solving a decade-long paroxysmal hypertension mystery: bladder paraganglioma - Li, Xingchen; Ding, Wuwu; Lv, Dong; Li, Hong (Frontiers in Oncology, 2025)
Bladder paraganglioma (BPGL) is an exceptionally rare neuroendocrine tumor whose diagnosis is often delayed or missed owing to its infrequent occurrence and variable clinical manifestations. We report a case of a 72-year-old female with a decade of unexplained paroxysmal hypertension, in which the diagnosis was ultimately prompted by an incidentally discovered bladder mass on ultrasonography. Crucially, 24-hour ambulatory blood pressure monitoring revealed micturition-triggered hypertensive crises, guiding subsequent confirmation through elevated post-voiding plasma-free metanephrines. The patient underwent successful laparoscopic partial cystectomy following careful preoperative alpha-adrenergic blockade, achieving complete symptom resolution postoperatively. This report underscores the diagnostic challenges inherent to BPGL, particularly the inconsistent presentation of classic micturition-related symptoms that can obscure the underlying trigger, emphasizing the utility of detailed history taking combined with targeted investigations, such as ABPM, to establish the diagnosis when initial catecholamine screenings may be unrevealing. Furthermore, this case reinforces the critical importance of meticulous preoperative preparation, multidisciplinary surgical management, and the necessity for considering genetic counseling and lifelong surveillance, given the potential for malignancy and hereditary predisposition associated with this condition.